Use of spinal manipulation in a rheumatoid patient presenting with acute thoracic pain: a case report - Chung, Chadwick L. R. (J Can Chiropr Assoc, 2015)
BACKGROUND: There is limited research related to spinal manipulation of uncomplicated thoracic spine pain and even less when pain is associated with comorbid conditions such as rheumatoid arthritis. In the absence of trial evidence, clinical experience and appropriate selection of the type of intervention is important to informing the appropriate management of these cases. CASE PRESENTATION: We present a case of a patient with long standing rheumatoid arthritis who presented with acute thoracic pain. The patient was diagnosed with costovertebral joint dysfunction and a myofascial strain of the surrounding musculature. The patient was unresponsive to treatment involving a generalized manipulative technique; however, improved following the administration of a specific applied manipulation with modified forces. The patient was deemed recovered and discharged with ergonomic and home care recommendations. DISCUSSION: This case demonstrates a clinical situation where there is a paucity of research to guide management, thus clinicians must rely on experience and patient preferences in the selection of an appropriate and safe therapeutic intervention. The case highlights the need to contextualize the apparent contraindication of manipulation in patients with rheumatoid arthritis and calls for further research. Finally the paper advances evidence based decision making that balances the available research, clinical experience, as well as patient preferences.